Taxing education in Ramsey's tradition - Wolfram F. Richter (Center for Economic Studies and ifo Institute (CESifo), 2009)
Assuming a two-period model with endogenous choices of labour, education, and saving, it is shown to be second-best efficient to deviate from Ramsey's Rule and to distort qualified labour less than nonqualified labour. The result holds for arbitrary utility and learning functions. Efficient incentives for education and saving are analysed under conditions of second and third best. It is argued that efficient tax policy should care more about incentives for education than for saving.
Keywords: H21; I28; J24; 330; Endogenous choice of education; labour; and saving; second-best efficient taxation; Power of Law of Learning; Bildungsverhalten; Arbeitsangebot; Sparen; Optimale Besteuerung; Lernprozess; Bildungsökonomik; Theorie